The Role of Innovation and Information Technology Capabilities in Increasing the Competitive Advantage of MSMEs Coffee Shops in Jakarta - Virgo Simamora; Indrianti Sulistianingsih (Budapest International Research and Critics University, 2022)
This research is an explanatory research that aims to explain the role of innovation capabilities and information technology in increasing the competitive advantage of MSMEs in Coffee Shops in Jakarta. The population of this research is all MSMEs of Millennia-owned coffee shops operating in the Jakarta area. The sampling technique used is a purposive sampling technique that uses certain criteria as a requirement to be a research sample. The data collection instrument used was a questionnaire distributed online via Instagram and WhatsApp. There are 215 coffee shop entrepreneurs in Jakarta who are willing to participate in this research. By using partial least squares structural equation modeling (PLS-SEM) the data is processed and results are obtained which show that innovation capability has a positive impact on competitive advantage in MSME Coffee Shops. Likewise, the results of this study explain that the capability of information technology has a positive impact on competitive advantage in MSME Coffee Shops in Jakarta.